Materiell og profesjonell stigmatisering av mennesker med sykelig overvekt - Christiansen, Wenche Skeivoll; Karlsen, Tor-Ivar; Larsen, Inger Beate (Nordisk tidsskrift for helseforskning, 2017)
The aim of this study is to show how people suffering from severe obesity mightexperience stigmatization. We interviewed 6 persons recruited from aNorwegian rehabilitation center, specialized in lifestyle intervention in severeobesity. We found that the participants suffering from severe obese experiencedstigmatization and thus felt that they a) did not fit into the materiel world and b)experienced a lack of respect from health care professionals. The results arediscussed according to how contemporary symbols are embedded in oursurroundings and in our bodies. The conclusion underlines severe obesity as acomplex problem which is strengthened by rooms and interior designed for idealsizes. The prejudices that health care professionals express worsen thesepatients feeling of stigma. We refer to this as material and professionalstigmatization.
Keywords: self-experience; health professions; material surroundings; severe obesity; stigma; egenerfaring; helsepersonell; materielle omgivelser; sykelig overvekt